The concept of gakliat tasdikat in the words of edification of Abay Kunanbayev - Н.Б., Мансуров; Б.Н., Темірханов (Journal of Oriental Studies, 2020)
The article analyzes the content of the thirty-eighth word of edification of the poet, enlightener Abay Kunanbaev, the founder of the Kazakh literary language. The analysis characterizes the embroidered ideas of the poet and their role in shaping the spiritual nature of the Kazakhs. And also the semantic meaning of the borrowed words and their meaning are examined and a comparative analysis is made relative to the original. For example, yaggar, iman, ichthyhad, sungat, etc. And the authors pertinently revealed the concept of the poet, which is based on reason and science, enlightening the formation of a good character in which people have different personalities. This is because the emphasis is on the need for special love to achieve science. Through these actions, he shows how he knew his creator and the environment. The authors suggest that Abay Kunanbayev, guided by the fact that those who have acquired knowledge, can recognize the truth and always grow up to be modern people, develop a scientific worldview, be recognized as a healthy and virtuous citizen who has not lost its relevance to this day. This is because the poet’s ideas in the words of edification will remain the indelible legacy of modern society. Key words: the book of words, history of language, mutual language, truth affirmation concept, love of science, mind and science.